Are health insurers in multiple lines of business less profitable? An examination of scope economies in health insurance. Issue 1 (21st November 2022) - Born, Patricia; Cook, Amanda; Sirmans, Tice; Yang, Charles
Abstract: In markets where companies can offer multiple products or services, production costs may decline, and profitability may increase as business scope expands. Using a sample of health insurers from 2015 to 2018 with data reported in the annual NAIC Supplemental Health Care Exhibit, we test whether scope economies exist among health insurers. We evaluate the relationship between scope and four profitability metrics—the medical loss ratio, the expense ratio, the underwriting profit ratio, and a profit efficiency measure obtained using a data envelopment analysis technique. We test two competing hypotheses from prior literature on scope economies in insurance. The strategic focus hypothesis states performance is higher for insurers that specialize in one line of business. The conglomeration hypothesis states performance is higher for insurers that operate in multiple lines of business. Our results provide evidence in support of the strategic focus hypothesis among US health insurers.